Analisis Implementasi Kebijakan Pembangunan Kawasan Perbatasan di Pulau Miangas dengan Pendekatan Kesejahteraan - Timpal, Felina Marthina; Hadiwijoyo, Suryo Sakti; Simanjuntak, Triesanto Romulo (Fakultas Ilmu Sosial dan Hukum, 2024)
This article aims to describe the Indonesia-Philippine border area on Miangas Island and analyze the Implementation of Border Area Development Policy on Miangas Island, Talaud Islands Regency, North Sulawesi Province. This article uses a qualitative descriptive research method with primary data obtained through interviews and Focus Group Disccussion and secondary data obtained through literature. This article uses a welfare approach through Welfare State theory and Geoeconomic concepts to analyze the implementation of border area management policies on Miangas Island which focuses on the government's role in efforts to improve the welfare of the people on Miangas Island.